Programa Educação Inclusiva Direito à Diversidade: estudo de caso sobre estratégia de multiplicação de políticas públicas. - Soares, Marcia Torres Neri (2010)
The multiplication strategy within the range of inclusion public policies from the Education Ministry - MEC, object of the present study, has been widely used in Brazil as a way of reaching all boroughs in this country of continental dimensions. According to the international guidelines, through different programs, the Education Ministry has adopted this strategy, in order to organize the multipliers formation, from boroughs that are situated in the five regions of the country. The research field of this study is specifically the Program Inclusive Education: the right to diversity - PEI: DD, established in Brazil by The Special Education Secretary Seesp-since 2003. Although this strategy has been current practice in the political actions of the federal government, the studies that hold the genesis, monitoring and knowledge of the multiplication process results in Brazil are still unknown. This investigation, conducted in the field of Cultural Studies and Inclusive Education, adopted the methodology Case Study and Grounded Theory for the theoretical construction based on data collected in the research field. Five boroughs, chosen as pole, were investigated : Salvador, Feira de Santana, Juazeiro, Vitoria da Conquista and Barreiras, from 2003 to 2008. The work was grounded on the qualitative research through the case study methodology. A total of 15 municipal representatives, one representative from the state and five, from the federal level participated in the research. The focus was a wide variety of evidences, as research techniques, besides the semi-structured interview, a survey of official documents and the change timeline were used by the participants who judged that there had been significant changes in their practice that could be associated to the Program, Media and the Research Diary- PDS, in which sensations and information were recorded under the researcher view in her research itinerary. The data were analyzed through similarities, contrasts and barriers among the boroughs that are field of the research. Considering the territorial dimension of our country, the findings indicate that there are similarities in the actions realized by the PEI boroughs: DD and the innumerable barriers inherent to the own administrative policy from the federal government that ties the multiplication agents. It also illuminates the urgency of the implementation of evaluative and comparative studies from the results of the multiplication strategy application to the public policies of inclusion, aiming to analyze its effectiveness at the national level and reset it to the local and regional reality, in addition to helping ensure the optimization of investment in improving the quality of education for all, including those with disabilities. The study also is expected to contribute to the advancement of the debate and knowledge on the area of public policies and, more specifically, the strategies of dissemination of inclusion educational policies in Brazil.